Pengembangan Sistem Informasi Berbasis Web Database Alumni - Ryan Permana; Ridho Dedy Arief Budiman; Dochi Ramadhani; Ade Akmalia Putra (Universitas Negeri Padang, 2022)
ABSTRACT Information technology is all forms of technology that help humans in terms of creating, storing, or disseminating information. Along with the times, information technology is more associated with high-speed computing and communication such as computers and mobile phones. The Institute of Teacher Training and Education of the Indonesian Teachers Association (IKIP-PGRI) Pontianak as an educational institution that requires information technology to assist activities within the Pontianak IKIP-PGRI environment. Based on the results of observations by conducting interviews, it is known that the study program has an information system website that contains information on study programs, but in the information system there are several shortcomings, namely the news and job vacancies have not been updated and there is no special alumni data information system to manage alumni data. Based on these problems, the researcher intends to develop a web-based information system for the alumni database using the R&D method and the ADDIE approach. The results of the system development were validated by 2 system experts to see the percentage of feasibility. The alumni information system has been tested for feasibility in terms of usability, functionality, and visual communication aspects. The overall average value in these aspects is 4.20 and 4.65, both values ​​are included in the